Eccrine Spiradenoma in Knee - A Sharma; P Sengupta; Anjan Kumar Das; Manish Kumar Nigam; S Chattopadhya (Wolters Kluwer Medknow Publications, 2014)
Eccrine spiradenoma is an uncommon benign adnexal tumor of the eccrine sweat glands. Although it can occur at any age, it is most common in young adults without any sex predilection. Malignant transformation is rare, presenting as rapid increase in size of a long-standing lesion. Here, we report a case of eccrine spiradenoma in a 35-year-old man who presented with swelling over the right knee, with cytological atypia but no recurrence until date.